2016
DOI: 10.3390/f7100249
|View full text |Cite
|
Sign up to set email alerts
|

Water, Rather than Temperature, Dominantly Impacts How Soil Fauna Affect Dissolved Carbon and Nitrogen Release from Fresh Litter during Early Litter Decomposition

Abstract: Abstract:Longstanding observations suggest that dissolved materials are lost from fresh litter through leaching, but the role of soil fauna in controlling this process has been poorly documented. In this study, a litterbag experiment employing litterbags with different mesh sizes (3 mm to permit soil fauna access and 0.04 mm to exclude fauna access) was conducted in three habitats (arid valley, ecotone and subalpine forest) with changes in climate and vegetation types to evaluate the effects of soil fauna on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…This study is primarily dedicated to calculate the general effects of litter mixture on its decay rates. Our results showed that the litter mixture widely demonstrates a non-additive effect, and most frequently synergistic effect, which is consistent with two previous review studies (Gartner & Cardon 2004;Li et al, 2016). Specifically, the decay rates of litter mixture are on average 2%-4% faster when compared to that of single litter species (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study is primarily dedicated to calculate the general effects of litter mixture on its decay rates. Our results showed that the litter mixture widely demonstrates a non-additive effect, and most frequently synergistic effect, which is consistent with two previous review studies (Gartner & Cardon 2004;Li et al, 2016). Specifically, the decay rates of litter mixture are on average 2%-4% faster when compared to that of single litter species (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Although experiments concerning the mixture effects on litter decomposition rates have been conducted in numerous individual studies, the conflicting results have hampered any possibility to draw general conclusions (Li et al, 2016). Most of conflicts could mainly result from the significant differences of influencing factors related to litter decompositions in experimental design (Barbe et al 2018, Leroy et al 2018, Zhao et al 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early decomposition stages, fresh litter input provides abundant food for the soil fauna and microorganisms. In addition, studies suggest that nutrient transport often occurs in the early decay stages (Hansson et al, 2010;Liao et al, 2016). Thus, the abundant food and efficient nutrient transport facilitate growth and activity of soil microorganisms, which ultimately produce a synergistic effect.…”
Section: The Non-additive Effect Across All Studiesmentioning
confidence: 99%
“…In addition, the specialization of soil fauna require favorable environmental factors, such as illumination, temperature, and moisture, which lead to differences in the HFA. Water, rather than temperature, impacts the effects of fauna on the carbon and nitrogen release from fresh litters during early litter decomposition [19]. For the HFA, the linkages between litter mass loss, nutrient release, and the soil's faunal community are not fully understood in temperate forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%